Introducing a multimodal perspective to emotional variables in second language acquisition education: Systemic functional multimodal discourse analysis - Liu, Zhengyuan (Frontiers in Psychology, 2022)
A systemic functional theory applied to multimodal discourse analysis (SF-MDA) is related to the theoretical and practical meaning extraction from the data showing how multiple semiotic resources are used in different modes of discourse ranging from textual, printed, and electronic texts to visual language and those existing alive as embedded in reality. In the present paper, we provide an introduction to the SF-MDA approach and then justify how it can benefit the second language acquisition (SLA) domain and more specifically the exploration of L2 affective variables. We will show how the SF-MDA approach fits in with the complexity and dynamic systems theory (CDST), and is capable of revealing the nuances of the developmental nature of the affective variables involved in language learning. The exemplary works of research in SLA domain using the SF-MDA approach are reviewed here as well as those exploring L2 affective variables. The further benefits of this approach will be emphasized at the end along with the implications it can have for the CDST-led line of research in applied linguistics.